Memorandum di Masa Pemerintahan Abdurrahman Wahid dalam Perspektif Hukum Tata Negara Islam - Misbahuddin Misbahuddin (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
The tide of democratization in Indonesia has radically changed the structure of Indonesian politics since the overthrown of New Order government by the reform movement in 1998. One important change is the essential vitality of parliamentary politics in Indonesia. In the era of Abdurrahman Wahid's government, the DPR's role was more independent and had a loud voice constraining the executive's running. As a result, the Indonesian constitution which is based on the Presidential system seems to have deviated to being a Parliamentary System. An example of tension is the birth of a memorandum. This paper seeks to examine the